Evaluation of a sprayable, ductile cement-based composite for the seismic retrofit of unreinforced masonry infills - Billington, Sarah L.; Kyriakides, Marios; Blackard, Ben; Willam, Kaspar; Stavridis, Andreas N.; Shing, P. Benson (My University, 2009)
A new retrofit technique for unreinforced masonry infills in non-ductile reinforced concrete frame structures is being investigated. The proposed technique uses a thin layer of sprayable, ductile fiber-reinforced mortar material referred to as Engineered Cementitious Composites, or ECC. The aim of the retrofit is to hold the masonry wall together to delay infill and frame strength degradation and enhance system ductility. Proof-of-concept experiments on retrofitted masonry prisms and beams demonstrated large increases in strength and ductility. Quasi-static, in-plane, cyclic testing of small-scale frames with masonry infills including 3 retrofit designs demonstrated a 10x increase in ductility in one design relative to the unretrofitted system. Results were used to design a retrofit for a 2/3-scale, in-plane test, where a 2.6× increase in ductility was achieved. Several finite element modeling approaches are under investigation for use in system predictions and further retrofit analyses. © 2009 ASCE.
Keywords: Reinforced concrete; Masonry materials; Infilled frame